Examining multicultural attitude and teaching outcome expectancy between TESL students minoring in counselling versus literature at Faculty of Education, UiTM Kampus Seksyen 17, Shah Alam / Zawani Badri - Badri, Zawani (Faculty of Education, 2011)
This study explores the comparison of multicultural attitude between TESL students minoring in counseling versus literature in order to see the effectiveness of subjects taught in these two distinguishing minor courses. This study employs quantitative-type of research methodology in which questionnaires consisted of thirty-seven items were distributed among fifty six final year students who had attended their teaching practicum before. From the findings, it can be interpreted that counseling students had portrayed similar multicultural attitude like their counterparts who take literature as their minor subjects. Besides, this study also investigates the multicultural teaching outcome expectancy between these two groups of respondents based on their recent teaching practicum experience. From the findings, it can also be inferred that multicultural teaching outcomes expectancy of counseling respondents are similar to literature respondents. In addition, this study also discovers the importance of attending any types of multicultural education in which TESL students who have experienced any multicultural education/training/course previously portrayed identical multicultural attitude like those who never attended any education/training/course before. Finally, novice teachers who taught in monocultural classroom portrayed the same multicultural teaching outcomes expectancy like their counterparts who taught culturally diverse classroom.